Lexico-Semantic Equivalence in Specialised Discourse: Translating English Economic Terminology into Karakalpak - Saparbaevich, Akhmedov Oybek; Kongratbayevna, Djumambetova Gulziba; Erjanovna, Seytnazarova Injayim (Masyarakat Linguistik Indonesia Universitas Andalas, 2026)
This research examines the lexical-semantic problems involved in translating economic terms from English into Karakalpak. The primary objectives of this study are to identify the main types of lexico-semantic difficulties in this domain and to describe how different translational solutions affect the accuracy, transparency, and functional stability of English–Karakalpak economic terminology. A qualitative, corpus-based methodology was applied, wherein empirical data was collected from specialised sources such as textbooks, financial reports, and dictionaries. The analysis involved structural, componential, and contextual examinations to classify the predominant translation strategies. The results demonstrate that terms are typically rendered through full lexico-semantic calques, partial calques, or pairs consisting of borrowed terms and native-based equivalents. Specifically, full calques effectively preserve internal conceptual meanings, while partial calques and borrowings reveal an ongoing tension between internationalisation and nationalisation. The significance of these findings lies in revealing that the translation of economic terms requires a careful balance between precise international comparability and national linguistic identity, as well as an awareness of instances of semantic shift, narrowing, or broadening. This research implies the informed adoption of a context-sensitive approach on the part of translators, terminologists and educators which takes into account their audiences and communicative purposes in order to preserve both professional accuracy as well as didactic accessibility within a developing Karakalpak terminological system.